Physical Properties, Chemical Properties, and Fertility of Soil under the Natural Stands of Ebony (Diospyros celebica Bakh.) - Asgar Taiyeb; Adam Malik; Imran Rachman; Muhardi Muhardi (Jurnal Penelitian Pendidikan IPA, 2025)
The soil physical and chemical properties and fertility under the natural stands of ebony were investigated from October 2022 to June 2024. The locations are the Gunung Sojol Nature Reserve and the Forest Management Unit of Sintuwu Maroso, Sulawesi. Ebony is dominant at all growth levels in Sintuwu Maroso, but only at pole level in Sintuwu Maroso as indicated by the IVI. The basal area and volume in Sintuwu Maroso are higher, indicating higher potential than Gunung Sojol. The medium texture soil with optimal moisture in Sintuwu Maroso also supports better growth than the coarse soil in Gunung Sojol. The soil in Gunung Sojol is characterized by acidic pH and high level of organic C, total P, total K, and Al-dd. Meanwhile, the soil in Sintuwu Maroso is slightly acidic with moderate levels of previous parameters. Despite high organic matter and CEC, the soil fertility of Gunung Sojol is hampered by low acidity and base saturation. While Sintuwu Maroso is challenged by low nutrient and organic matters. In general, both locations have moderate soil fertility. The results can serve as a basis for effective cultivation and conservation strategies for both in-situ and ex-situ methods